The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsomega.9b01906
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Studies, and α-Glucosidase Inhibitory, Antidiabetic, and Antioxidant Activities of 2,3-Dihydroquinazolin-4(1H)-ones Derived from Pyrazol-4-carbaldehyde and Anilines

Abstract: A series of new quinazoline derivatives were designed and synthesized via a one-pot condensation reaction between isatoic anhydride and aromatic aldehydes with anilines using aluminum sulfate as a catalyst in refluxing ethanol. Their structures were confirmed by their physical, IR, 1H NMR, 13C NMR, and mass spectroscopy data and evaluated for some biological effects, including the antioxidant and α-glucosidase inhibitory activities as well as some in vivo hematological parameters. The ability of synthesized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 74 publications
(148 reference statements)
0
21
0
Order By: Relevance
“…Results shows that all compounds 1 – 10 are excellent inhibitors of α‐glucosidase with IC 50 in the range of 45.8–74.5 μ M compared to standard 1‐deoxynojirimycin (DNJ) with an IC 50 value of 425.6 μ M. Study reveals that precursor enoxacin exhibit and IC 50 value of 58.9 μ M while substitution of benzyl group as in compound 1 increases the inhibition potential to a small extent with an IC 50 value of 57.8 μ M. Substitution of chloro at meta and para position as in molecules 5 , bromo at ortho 6 and fluoro at ortho and para position 8 on benzyl further increased the inhibition potentials IC 50 values 52.7, 45.8 and 48.7 μ M. Whereas compounds 2 , 3 , 4 , 7 , 9 and 10 were found to have higher IC 50 values in the range of 59.8‐74.5 μ M. Compound 6 was found to be a most potent inhibitor of α ‐glucosidase with an IC 50 value 45.8 μ M. Studies found that position and nature of substituent group shows effect on inhibition potential [40–43] . It is suggested that little variation in hydrogen bonding between protein active sites and synthetic compounds are responsible for variation in inhibition potential of these compounds against α ‐glucosidase [44–46] .…”
Section: Resultsmentioning
confidence: 95%
“…Results shows that all compounds 1 – 10 are excellent inhibitors of α‐glucosidase with IC 50 in the range of 45.8–74.5 μ M compared to standard 1‐deoxynojirimycin (DNJ) with an IC 50 value of 425.6 μ M. Study reveals that precursor enoxacin exhibit and IC 50 value of 58.9 μ M while substitution of benzyl group as in compound 1 increases the inhibition potential to a small extent with an IC 50 value of 57.8 μ M. Substitution of chloro at meta and para position as in molecules 5 , bromo at ortho 6 and fluoro at ortho and para position 8 on benzyl further increased the inhibition potentials IC 50 values 52.7, 45.8 and 48.7 μ M. Whereas compounds 2 , 3 , 4 , 7 , 9 and 10 were found to have higher IC 50 values in the range of 59.8‐74.5 μ M. Compound 6 was found to be a most potent inhibitor of α ‐glucosidase with an IC 50 value 45.8 μ M. Studies found that position and nature of substituent group shows effect on inhibition potential [40–43] . It is suggested that little variation in hydrogen bonding between protein active sites and synthetic compounds are responsible for variation in inhibition potential of these compounds against α ‐glucosidase [44–46] .…”
Section: Resultsmentioning
confidence: 95%
“…Quinazolines have a broad range of pharmacological applications, in addition to their low toxicity profiles [ 3 ]. Quinazoline frameworks have great pharmacological activities as antioxidant [ 7 , 8 , 9 ], antidiabetic [ 10 , 11 , 12 ], antibacterial [ 13 , 14 , 15 ], antiviral [ 16 , 17 , 18 ], antimicrobial [ 19 , 20 , 21 ], anticancer [ 22 , 23 ], antihistaminic [ 24 , 25 , 26 ], antidiuretic [ 27 , 28 ], antitubercular [ 29 , 30 , 31 ], and anti-inflammatory [ 32 , 33 , 34 ] agents. Quinazolinones are a type of quinazoline derivative that are biologically active in the same way as quinazoline [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the prescribed antidiabetic drugs are responsible for various side effects such as liver problems, diarrhea, lactic acidosis, and high rate of secondary failure. So that, the discovery of novel small molecules with potential usefulness as potent hypoglycemic agents is still a major challenge to medicinal chemistry researchers (Barmak, Niknam et al 2019).…”
Section: Introductionmentioning
confidence: 99%